Чернігівські сіверяни - Казаков, А.Л. (Археологія і давня історія України, 2020)
У статті йдеться про місця знаходження у Чернігові артефактів, що мають безпосереднє відношення до носіїв роменської археологічної культури, яку традиційно ототожнюють із літописними сіверянами. Issues considers the emerging of East Slavic cities is one of the main challenges for contemporary Medieval studies. This challenge refers mainly to Polians, Drevlians, Severians and other tribes and tribal unions which are mentioned in some of Kyiv Rus manuscripts. The paper deals with the description of localization and finding in Chernihiv city the artifacts defined as the ones belonging to Romenska culture, which, in historical studies, identified as Severians (who was mentioned by Primary Chronicle).